Medication use from conception to the first antenatal appointment: agreement between maternal self-report to midwife and prescribing records in Northern Ireland in 2011-2016 - Given, Joanne; Dolk, Helen; Little, Alison; Loane, Maria (International journal of population data science, 2025)
IntroductionData reliability must be considered before using administrative healthcare databases to study medication utilisation and safety during pregnancy. ObjectivesTo compare medication use reported by the mother and recorded by midwives at the first antenatal visit in the Northern Ireland (NI) Maternity System (NIMATS) to dispensed prescriptions recorded in the Enhanced Prescribing Database (EPD). MethodsA population-based linked cohort study including all resident women in NI who gave birth between 01/01/2011 and 31/12/2016. Prescriptions dispensed in the EPD between the last menstrual period and the first antenatal visit were compared to medications recorded in NIMATS. The number and proportion of pregnancies with medications in each data source were calculated along with Cohen's kappa, sensitivity and specificity. ResultsOf the 139,687 pregnancies in NIMATS (106,206 women), 74.3% reported taking medication, including supplements, and 63.5% had prescriptions dispensed (with 86.9% reporting taking medication or having a prescription dispensed). Excluding supplements, 18.2% reported medication use, while 48.7% had prescriptions dispensed. In NIMATS, 20.4% of pregnancies had vitamins and 1.2% antacids compared to 1.4% and 0.1% respectively in EPD. All other medications were more commonly prescribed than reported, with moderate agreement for antiemetics (kappa 0.42, 95% CI 0.41-0.43), anticoagulants (kappa 0.62, 95% CI 0.61-0.64) and antihypertensives (kappa 0.62, 95% CI 0.61- 0.64). Agreement was lowest for 400mg folic acid (kappa -0.09, 95% CI -0.10 - -0.09). There was considerable underreporting of medicines for chronic use, such as antiepileptics, at the first antenatal appointment. ConclusionsMedication use during early pregnancy was common. Women obtained vitamins and antiacids over the counter rather than by prescription, but all other medications were prescribed more. Non-compliance and discontinuation may explain some of the disagreement, but reporting of prescribed medicines for chronic illnesses was incomplete in antenatal records. To identify all medication use, combining maternal reporting with prescribing data is recommended.